Criminalization of Perpetrators of the Crime of Theft with Pancasila Aggravation (Criminal Case Study Decision Number: 401/Pid.B/2024/PN Bgl) - Purba, Ruth Cheline Eglesya; Hanim, Lathifah (UNISSULA Semarang, 2025)
Abstract. Law is a norm or rule that contains mandatory legislation and anyone who violates the article will receive legal sanctions. The legal subjects who are to be prosecuted are not only those who have actually committed unlawful acts, but also legal acts that may arise and equip the state to act in accordance with the laws currently in force. The crime of theft itself is regulated in Article 362 of the Criminal Code and the crime of aggravated theft is regulated in Article 363 of the Criminal Code. The crime of theft is one of the types of crimes in Indonesia, this violation is regulated in Article 362 of the Criminal Code. There are many ways to classify the types of theft crimes, one of which is the crime of theft with its level adjusted according to Article 363 of the Criminal Code Research from the case study of decision no. 401/Pid.B/2024/PN Bgl discusses a theft case that occurred in Bengkulu City. On Monday, July 8, 2024, at around 02.00 WIB, the defendant Oki Dwi Saputra alias Oki bin Nasrah committed theft at a house located on Jalan Beringin Rt.06 Rw.03, Padang Jati, Ratu Samban District, Bengkulu City. At that time, the victim was sleeping in his house. The defendant who was walking home passed the victim's house and saw the kitchen door open. Using this oportunity, the defendant entered the victim's house without permission and took two cellphones, namely one Vivo Y66 unit in rose gold and white and one Realme unit in gray. After successfully taking the two cellphones, the defendant immediately ran out of the house. The victim, who realized that his belongings had been taken, shouted